Development and Validation of RP-HPLC Method for the Determination of Related Compounds in Quetiapine Hemifumarate Raw Material and Tablets - Paulo Cesar Pires Rosa, Iury Fernando Rodrigues Pires, Blanca Elena Ortega Markman, Fábio Ferreira Perazzo (Journal of Applied Pharmaceutical Science, 2013)
A simple and sensitive high performance liquid chromatographic method has been developed for the determination of assay quantitative of related compounds and quetiapine hemifumarate in raw material and tablets. Quetiapine hemifumarate is used for the treatment of schizophrenia and there are some generic medicines available in brazilian marketing pharmaceutical, it´s necessary evaluate the quality control of raw material used in the production. Efficient chromatographic separation was carry out on a C18 stationary phase with mobile phase consisting in a mixture of phosphate buffer pH 6.6:Acetonitrile:Methanol (45:40:15), flow rate of 1.0 mL min-1, injection volume of 20 µL, temperature of 25 °C and ultraviolet detection at 220 nm. All of the chromatographic parameters were attended, with resolution greater than 2.9 between quetiapine hemifumarate and impurities. The HPLC method was validated according ICH guidelines, evaluating selectivity, limits of detection and quantification, linearity, accuracy, precision and robustness. The relative retentions times were about 0.58, 0.69 and 0.88 to related compounds, piperazine, lactam and ethanol compound, respectively. Impurities were found < 0.1 % in samples and the assay of quetiapine hemifumarate was > 98.15%. The method can be used for the routine analysis of the impurities in Quetiapine hemihumarate (QH) without any interference.
Keywords: Quetiapine hemifumarate, high performance liquid chr